Revisiting the relationship between constructive alignment and learning approaches: A perceived alignment perspective. - Christian Stamov Roßnagel (Public Library of Science (PLoS), 2021)
The constructive alignment (CA) of university teaching is designed to encourage students to adopt a deep learning approach, which supports meaningful learning. The evidence is mixed, however, with some studies showing that students may adopt a surface approach even when teaching promotes deep learning. To add to the understanding of the relationships between CA and learning approaches, we explored with quantitative measures two potential implications from prior qualitative research. First, we assessed with a novel questionnaire if students' CA perceptions predicted adaptation towards a deep learning approach. Second, we explored relationships between deep approach adaptation and learning motivation, as well as perceived mental workload. 56 students from two second-year courses in different study programmes completed a learning approach questionnaire in the second (T1), seventh (T2), and the final fourteenth (T3) course week. At T2 and T3, participants also rated the constructive alignment of the course, their learning motivation, and the mental workload. Regression analyses showed that ILO Clarity (i.e. being clear about the intended learning outcomes of the course) and receiving effective feedback were associated with a significant increase in deep approach scores from T2 to T3. That deep approach adaptation was in turn positively related to learning motivation in terms of higher ratings of one's competence, the importance of high course performance, and course usefulness. Moreover, deep approach adaptation went with higher satisfaction of having accomplished one's learning goals, but also with stronger feelings of insecurity and stress. Our findings suggest that students' CA perceptions are meaningful predictors of learning approach adaptation that might eventually be developed into indicators of the effectiveness of CA implementation at the course level.